Synthesis and Characterization of Mixed Ligand Copper(II) Complexes of Hippuric Acid and Nitrilotriacetic Acid - Kumar, G.; N. Srivastava, M. (Asian Journal of Chemistry, 2010)
Mixed ligand copper(II) complexes, Na2[Cu(C6H5CONHCH2COO)N(CH2COO)3].4H2O and Na2[Cu(C6H5CONHCH2COO N(CH2COO)3] formed with hippuric acid and nitrilotriacetic acid have been synthesized and characterized by their elemental analysis, spectral (IR, electronic and 1H NMR spectra) and magneto-chemical studies. Hippuric acid acts as a bidentate ligand and the coordination occurs through carboxylate oxygen and the nitrogen of the amido group. Nitrilotriacetic acid shows tetradentate behaviour by coordination through three carboxylate oxygen atoms and the nitrogen atom. The complexes have been suggested to show octahedral structures.